DOUBLE DE-MOTIVATION AND INTRINSIC MOTIVATION AMONG TEACHERS IN INDONESIA - Leo Marai (Faculty of Psychology, Universitas Gadjah Mada, 2001)
The “double de-motivation” hypothesis (Carr & MacLachlan, 1993/4; MacLachlan & Carr, 1993) has empirically been established by recent studies (e.g., Carr et al., 1996; McLoughlin & Carr, 1997), however, the other motivational effects on organizational dynamics that this phenomenon symbiosis with has not been explored. One principal human factor that has direct link to double de-motivation is intrinsic motivation. Therefore, this study was conducted to investigate the double de-motivation hypothesis and intrinsic motivation among English teachers in Indonesia. A total of 188 participants responded to Carr et al’s (1996) pay and job satisfaction scale and Morse and Weiss’s (1955) Lottery Questionnaire (LQ). Based on pay differential criteria derived from the first segment of pay and job satisfaction scale, expatriate and local teachers were classified into underpaid (n = 66, local teachers), overpaid (n = 60, expatriate teachers), and equitable paid (n = 62, local and expatriate teachers) groups. On the basis of theoretical and literature review of double de-motivation and intrinsic motivation, two hypotheses emerged in this study. First, to replicate double de-motivation, it was predicted that the underpaid and overpaid groups will be de-motivated, thus experiencing double de-motivation as compared with the equitable paid group. The results supported the hypothesis and showed distinctively that the underpaid and overpaid groups were significantly less satisfied or de-motivated than equitable paid group, thus confirming the existence of double de-motivation. Second, it was predicted that the underpaid and overpaid groups will possess less intrinsic motivation as compared to the equitable paid group. The results revealed that both the underpaid and overpaid groups possessed significantly lower level of intrinsic motivation than equitable paid group. The findings are discussed in relation to organisational management for inequity in salary, and the shortcoming of the study is highlighted with a concluding recommendation. Key words: double de-motivation, inequity, intrinsic motivation